Development of Nabr Al-Ashwat Al-Arabiyyah Materials to Enhance the Arabic Speaking Skills of Students - Muhajir Muhajir; Alimudin Alimudin; Era Sastra Pangestu; Rafidah Abdullah (Arabic Education Department, Islamic Studies Faculty, Universitas Muhammadiyah Malang, 2023)
The purpose of this study was to determine how the development of nabr al-ashwat al-arabiyyah material improved the Arabic speaking skills of Muhammadiyah 3 Yogyakarta Junior High School students. This research utilised a research and development method with the ADDIE model, namely analysis, design, development, implementation and evaluation. The data collection process employed observation, questionnaires, interviews and tests. The results explain that judging from the average pre-test value, it can be said that nabr material has proven effective in improving the speaking proficiency of the material Arabic lessons in grade IX of Muhammadiyah 3 Yogyakarta Junior High School students. The researcher concluded that the development of nabr material from the pre-test results obtained an average value (mean) of 60.27, the minimal value being 48, the maximum value being 70 and the standard deviation being 6.036. while in the post-test table the average student score (mean) is 82.77, the minimum value being 70.00, the maximum value being 98.00 and the standard deviation being 8.149, which was proven by the effectiveness test using the JASP application. The paired samples t-test showed an increase in self-regulation (t (36) = -21.761, p <.001). This data shows that the p-value is <0.05; hence, it can be concluded that the data is significant. Furthermore, the Cohen's d table shows an effect of -3.627.